Good practices in perinatal care and breastfeeding protection during the first wave of the COVID-19 pandemic: a national situation analysis among BFHI maternity hospitals in Spain - Barbara Muñoz-Amat; Carmen Rosa Pallás-Alonso; María-Teresa Hernández-Aguilar (International Breastfeeding Journal, 2021)
Abstract Background Although the positive effects of good clinical quality standards in perinatal care and breastfeeding support for women, newborns and families have been already demonstrated, many of these practices were disrupted during the COVID-19 pandemic. The objective of this study was to analyse the impact of the COVID-19 pandemic on perinatal care and breastfeeding support practices offered by the Spanish maternity hospitals committed to the UNICEF Baby-friendly Hospital Initiative (BFHI), to women with and without COVID-19. Methods Implementation of perinatal practices was assessed by a cross-sectional survey conducted in May 2020 using an online questionnaire. Comparison with pre-pandemic situation and level of commitment to BFHI practices was performed. Results Response rate was 50% (58/116). Mothers with COVID-19 suffered greater restrictions in the practices compared to women without COVID-19, with lower rates of companion of choice during labour (84% vs 100%; p = 0.003), skin-to-skin contact (32% vs 52%; p = 0.04), rooming-in (74% vs 98%; p <  0.001), companion of choice during hospital stay (68% vs 90%; p = 0.006), and breastfeeding support (78% vs 94%; p = 0.02). Practices were significantly less prevalent in COVID-19 mothers compared to pre-pandemic situation. A lower accompaniment rate was observed in non-COVID-19 group during delivery (24% vs 47.9%; p <  0.01). Hospitals with higher commitment to BFHI practices reported higher rates of skin-to-skin contact (45.2% vs 10.5%; p = 0.01) and rooming-in (83.9% vs 57.9%; p <  0.05) in COVID mothers. Fewer restrictions were observed in hospitals located in the regions where the pandemic hit harder. In these regions there was a significantly higher level of BFHI commitment of the hospitals, but no significant differences were observed in the average size of the hospital. All the practices suffered even more restrictions during the first weeks of the pandemic. Conclusion All mothers suffered restrictions in perinatal care during the COVID-19 pandemic. Women with COVID-19 infection suffered more restrictions in perinatal practices than women without infection. The degree of commitment to WHO-UNICEF perinatal quality standards, integrated into the BFHI, was associated with maintenance of good clinical practices.